Pharmaceutical Prospects of Bee Products: Special Focus on Anticancer, Antibacterial, Antiviral, and Antiparasitic Properties - Nainu, Firzan (Antibiotics (Basel), 2021)
Bee products have long been used in traditional healing practices to treat many types of disorders, including cancer and microbial-related diseases. Indeed, several chemical compounds found in bee products have been demonstrated to display anticancer, antibacterial, antiviral, and antiparasitic properties. With the improvement of research tools and in view of recent advances related to bee products, this review aims to provide broad yet detailed insight into the pharmaceutical prospects of bee products such as honey, propolis, bee pollen, royal jelly, bee bread, beeswax, and bee venom, in the domain of cancer and infectious disease management. Available literature confirms the efficacy of these bee products in the alleviation of cancer progression, inhibition of bacterial and viral proliferation, and mitigation of parasitic-related symptoms. With such potentials, bioactive components isolated from the bee products can be used as an alternative approach in the long-run effort to improve humans’ health at a personal and community level.